Soldiers alive - Ishikawa, Tatsuzō, 1905-1985 (University of Hawaiì Press, 2003)
"When the editors of Chuo koron, Japan's leading liberal magazine, sent the prizewinning young novelist Ishikawa Tatsuzo to war-ravaged China in early 1938, they knew the independent-minded writer would produce a work wholly different from the lyrical and sanitized war reports then in circulation. They could not predict, however, that Ishikawa would write an unsettling novella so grimly realistic it would promptly be banned and lead to the author's conviction on charges of "disturbing peace and order.""--Jacket